Peningkatan Keamanan pada Simple Network Time Protocol (SNTP) untuk Mendeteksi Cybercrime di dalam Aktivitas Jaringan: Improved Security on Simple Network Time Protocol (NTP) to Detect Cybercrime in Network Activity - Kotim Subandi; Victor Ilyas Sugara; Adriana Sari Aryani (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
Today's cybercrime methods are extremely diverse. The methods employed by attackers are becoming more diverse and intricate. Malicious software, commonly referred to as malware, is utilized in these various attacks. Malware threats and their propagation can be accomplished in several different ways. Good governance facilitates prevention via migration, assisting the security team and network infrastructure IT. This paper discusses efforts to enhance the security of the Simple Network Time Protocol (SNTP) to detect cybercrime on the network. Based on the results of the conducted experiments, we determined that by updating the Simple Network Time Protocol, implementing the client-server antivirus, and scanning every client connected to the local network or centrally, we could detect the types of attacks that frequently occur on the network system, thereby protecting all client computers from malware, viruses, worms, and Trojan horses. Based on the antivirus migration data, the employed research method can find information on cybercrimes that involve malware that enters the network and is successfully cleaned or quarantined before being automatically blocked.